Nurturing Difference: The Autistic Student in Professional Writing Programs - Andrea Greenbaum (Journal of the Assembly for Expanded Perspectives on Learning, 2010)
can assist autistic students by providing them with writing opportunities through the classroom, internships, and university publications. Aiding their personal and professional development also serves the university and the community-at-large.